PEMODELAN ALJABAR MAX-PLUS DAN EVALUASI KINERJA JARINGAN ANTRIAN FORK-JOIN TAKSIKLIK DENGAN KAPASITAS PENYANGGA TAKHINGGA - ANDY RUDHITO, M.; WAHYUNI, SRI; SUPARWANTO, ARI; SUSILO, F. (Jurnal Matematika; Vol 1 No 1 (2010), 2012)
This paper aims to model and determine the service cycle completion time of noncyclic fork-join queueing networks with infinite buffer capacity, using max-plus algebra. The finding show that the dynamics of the noncyclic fork-join queuing networks with infinite buffer capacity can be modeled into a matrix equation over max-plus algebra. We can also show that the service cycle completion time of queuing networks is a max-plus eigenvalues of the matrix in the equation.slklsklslsllsllllllllllllllllllllll
Keywords: max-plus algebra, max-plus eigenvalues, fork-join queueing networks, service cycle completion time.